Glucose and lactate metabolism in the awake and stimulated rat: a 13C-NMR study - Sampol, Denys; Ostrofet, Eugenius; Jobin, Marie-Lise; Raffard, Gérard; Sanchez, Stéphane; Bouchaud, Véronique; Franconi, Jean-Michel; Bonvento, Gilles; Bouzier-Sore, Anne-Karine (Frontiers in Neuroenergetics, 2013)
Glucose is the major energetic substrate for the brain but evidence has accumulated during the last 20 years that lactate produced by astrocytes could be an additional substrate for neurons. However, little information exists about this lactate shuttle in vivo in activated and awake animals. We designed an experiment in which the cortical barrel field (S1BF) was unilaterally activated during infusion of both glucose and lactate (alternatively labeled with 13C) in rats. At the end of stimulation (1h), both S1BF areas were removed and analyzed by HR-MAS NMR spectroscopy to compare glucose and lactate metabolism in the activated area versus the non-activated one. In combination with microwave irradiation, HR-MAS spectroscopy is a powerful technical approach to study brain lactate metabolism in vivo. Using in vivo 14C-2-deoxyglucose and autoradiography, we confirmed that whisker stimulation was effective since we observed a 40% increase in glucose uptake in the activated S1BF area compared to the ipsilateral one. We first determined that lactate observed on spectra of biopsies did not arise from post-mortem metabolism. 1H-NMR data indicated that during brain activation, there was an average 2.4-fold increase in lactate content in the activated area. When [1-13C]glucose+lactate were infused, 13C-NMR data showed an increase in 13C-labeled lactate during brain activation, as well as an increase in lactate C3-specific enrichment. This result demonstrates that the increase in lactate observed on 1H-NMR spectra originates from newly synthesized lactate from the labeled precursor ([1-13C]glucose). It also shows that this additional lactate does not arise from an increase in blood lactate uptake since it would otherwise be unlabeled. These results are in favor of intracerebral lactate production during brain activation in vivo, which could be a supplementary fuel for neurons.